ANALISIS KEMAMPUAN PENGGUNAAN JOUKEN HYOUGEN MAHASISWA PRODI PENDIDIKAN BAHASA JEPANG ANGKATAN 2020 UNIVERSITAS NEGERI PADANG - Sania Sania; Meira Anggia Putri (Universitas Negeri Padang, 2023)
The study is in the background of Jouken Hyougen, which has the same meaning, so students have difficulty distinguishing the use of a form of reinforcement in a sentence. This study aims to describe the ability to use jouken hyougen (to, ba, tara, and nara) by Japanese language students in the class of 2020 at the Japanese Language Education study program at Padang State University. The kind of research used in this study is a descriptive method whose data is in the form of scores. The population in this study is the 2020s Japanese language students of the 2020 class of Padang State University of 51. The sample in this study uses the full sampling population, in which the entire population is sampled by 2020 Japanese education students of Padang State University, conducted by 35 people. The data in this study is the value of the results of the test capability to use jouken hyougen at a 2020 Japanese language education Padang State University. Based on the results of the study conducted, the overall ability of the 2020 Japanese language education department at Padang State University is 'less' qualified, with an average value of 47.43. Keywords: Ability, Jouken Hyogen, Japanese language